Best pulse selection of photoplethysmography signal through comparative method - Nurhafizah, Mahri; Gan, Kok Beng, Dr.; Mohd. Alauddin, Mohd. Ali, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/